ANALYSIS GLOBAL BUSINESS CYCLE AND FISCAL RISKS : An Empirical Study of ASEAN-5 - Aulia, Sarah; Kurnia, Akhmad Syakir (JURNAL DINAMIKA EKONOMI PEMBANGUNAN, 2018)
This thesis aims to analyze global business cycle and fiscal risk in ASEAN-5 which is expected to be explained by several explanatory variables including primary balance/GDP, oil price, economic growth, output gap, and LIBOR interest rate. More spesifically, this thesis focus on the effect of oil price with Debt/GDP is a benchmark ofÂ  fiscal risk. This research used panel data of ASEAN-5 period 2000-2014. Prior to conducting the analysis, this study looked at the correlation coefficients between the cycle components (output gap) and the primary balance per GDP to identify the fiscal policy character in each country. The cycle component is calculated by using the difference between original series and trend components using Hodrick Prescott Filter. The fiscal policy characteristics of Indonesia, Malaysia, Phillipines, and Thailand apply procyclical policies while singapore implements countercyclical fiscal policy.Â The results of the analysis conducted using the fixed effect method show the global business cycle and world oil price fluctuations affect the fiscal risks. The results of this study indicate when the business cycle in a state of booming domestic governments tend to increase government spending and create fiscal risks. Meanwhile, the LIBOR and Primary Balance rate per GDP which is a variable derivative of the fiscal suistanability concept has an effect on fiscal risk. However, economic growth has no effect because the current debt is the tax burden in the future.